Stability of Perovskite Solar Cells: Degradation Mechanisms and Remedies - Mazumdar, Sayantan; Zhao, Ying; Zhang, Xiaodan (Frontiers in Electronics, 2021)
Inorganic-organic metal halide perovskite light harvester based perovskite solar cell has come to the limelight of solar cell research due to its rapid growth in efficiency. The present efficiency is challenging the Si-based or thin film based commercial devices. But, commercialization of perovskite solar cells remains elusive due to lack of stability of these devices under real operational conditions, especially in long time use. A huge number of researchers engaged in an ardent effort to improve the stability of the perovskite solar cells. Understanding the degradation mechanisms has primary importance before exploring the remedies for degradation. In this review, a methodical understanding of various degradation mechanisms of perovskites and perovskite solar cells are presented followed by a discussion on different steps taken to overcome the stability issues. Latest insights on degradation mechanisms are discussed. Various approaches of stability enhancement are reviewed with emphasis on reports which complied with operational standard for practical application in commercial solar module. Operational stability standard enacted by International Energy Commission is especially discussed with reports which met the requirements or showed excellent results, which is the most important criterion to evaluate a device’s actual prospect to be utilized for practical application in commercial solar modules. An overall understanding of degradation pathways in perovskite and perovskite solar cells and steps taken to overcome those with references including state-of-the art devices with promising operational stability, can be gained from this review.